PENGARUH KEADILAN, DISKRIMINASI, DAN KEMUNGKINAN TERDETEKSI KECURANGAN TERHADAP PERSEPSI WAJIB PAJAK MENGENAI PENGGELAPAN PAJAK PENGHASILAN (TAX EVASION) (Studi Kasus Pada WPOP Yang Melakukan Kegiatan Usaha di Kabupaten Kendal) - Dhiny Nur Halifah; Nur Sayidah (Fakultas Ekonomi Universitas IBA Palembang, 2021)
The purpose of this study was to analyze the effect of justice, discrimination and the possibility of fraud detection on taxpayers' perceptions of income tax evasion (tax evasion). Tax evasion is a taxpayer's way of reducing or even eliminating the amount of tax owed. The population in this study were individual taxpayers in Kendal Regency. The sampling method was carried out by convenience sampling technique. The sample in this study is an individual taxpayer who conducts business activities in Kendal Regency, amounting to 43 people. The results of this study indicate that justice, discrimination and the possibility of fraud detection simultaneously have a significant effect on income tax evasion (tax evasion) as evidenced by a significant value of 0.000 <0.05. Partially fairness has no significant effect on income tax evasion (tax evasion), this is evidenced by a significant value of 0.787> 0.05, discrimination has a significant effect on income tax evasion (tax evasion) as evidenced by a significant value of 0.000 <0.05 and the possibility of fraud detection significant effect on income tax evasion (tax evasion) as evidenced by a significant value of 0.000 <0.05.